Computational analysis of Allium sativum compounds to identify thermolabile hemolysin inhibitors against Vibrio alginolyticus in shrimp - Sayed Mashequl Bari; Nafees Bin Reza; Meamaching Marma; Sk. Foisal Ahmed; Md Arif Hussain; Md Naimuddin Jabed; Md Alomgir Hossain; Maria Manzoor; Md Saiful Alam (Journal of Advanced Biotechnology and Experimental Therapeutics)
Vibrio alginolyticus is one of the major disease-causing bacteria in shrimp aquaculture. The widespread use of antibiotics in shrimp aquaculture to treat bacterial diseases has raised concerns about antibiotic resistance. As a result, alternative treatments, such as plant extract phytochemicals are being explored to mitigate these risks. This study aims to identify promising biologically active compounds from garlic (Allium sativum) that can inhibit the virulent protein thermolabile hemolysin of V. alginolyticus, which causes shrimp vibriosis. Various computational approaches, including molecular docking, pharmacokinetic analysis, and molecular dynamics simulation, were conducted to predict the compounds that can inhibit the phospholipase and hemolysis activities of the thermolabile hemolysin protein. Out of thirty-five compounds from A. sativum, protopine (CID 4970), gibberellin A7 (CID 92782), and gibberellic acid (CID 6466) demonstrated the strongest binding affinities, with scores of -9.4, -8.0, and -7.4 kcal/mol, respectively. Pharmacokinetic and toxicity analyses showed favorable drug-like properties for gibberellin A7 and gibberellic acid with no violations. Molecular dynamics simulations demonstrated that gibberellin A7 and gibberellic acid exhibited the highest stability over 100 nanoseconds. The investigation shows that gibberellin A7 and gibberellic acid from A. sativum have the potential to inhibit the virulent activity of thermolabile hemolysin. However, the study needs further in-vitro and in-vivo analysis to test our predicted results. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 1-17]